2021
DOI: 10.1186/s12871-021-01259-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a predictive score for ICU delirium in critically ill patients

Abstract: Background The incidence of delirium in intensive care unit (ICU) patients is high and associated with a poor prognosis. We validated the risk factors of delirium to identify relevant early and predictive clinical indicators and developed an optimized model. Methods In the derivation cohort, 223 patients were assigned to two groups (with or without delirium) based on the CAM-ICU results. Multivariate logistic regression analysis was conducted to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…The factors identified in this study that were involved in the development of delirium were consistent with existing risk factors for developing delirium in the ICU and included higher age, higher clinical frailty score, lower BMI, greater dementia, high APACHE II score, increases ventilator use, and greater sleep disturbances. [39][40][41][42][43][44] Findings of previous studies suggest that dexmedetomidine prevents delirium. [45][46][47] However, in the present study, adjusted Cox regression analyses revealed a lack of delirium prevention by dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…The factors identified in this study that were involved in the development of delirium were consistent with existing risk factors for developing delirium in the ICU and included higher age, higher clinical frailty score, lower BMI, greater dementia, high APACHE II score, increases ventilator use, and greater sleep disturbances. [39][40][41][42][43][44] Findings of previous studies suggest that dexmedetomidine prevents delirium. [45][46][47] However, in the present study, adjusted Cox regression analyses revealed a lack of delirium prevention by dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…Delirium is commonly seen in critically ill patients and is clinically diagnosed using screening tools, such as the Confusion Assessment Method for the ICU (CAM-ICU) or the Intensive Care Delirium Screening Checklist (ISDSC). Zhang et al reported sepsis as a risk factor for delirium in ICU patients; others reported risk factors include a history of hypertension, hypoxemia, use of benzodiazepines, deep sedation, and mechanical ventilation [98].…”
Section: Deliriummentioning
confidence: 99%
“…A presença de pelo menos um desses achados anormais de EEG foi associada a um aumento significativo na chance de delirium (42 vs 15%, p=0,006). Zhang et al (2021) desenvolveram e validaram um modelo preditivo de delirium, que inclui seis preditores avaliados na admissão na UTI: (1) história de hipertensão, (2) hipoxemia, (3) uso de benzodiazepínicos, (4) sedação profunda, ( 5) sepse e (6) ventilação mecânica. O modelo matemático previu o delirium na UTI de forma confiável (0,862, p<0,001) na coorte de derivação e 0,739 (P < 0,001) na coorte de validação; contribuindo com o diagnóstico de delirium e a tomada de medidas precoces.…”
Section: Identificaçãounclassified